Resolving Acuticulata (Metridioidea: Enthemonae: Actiniaria), a clade containing many invasive species of sea anemones - Isabel A. M. Pen; Charlotte Benedict; Michael B. Broe; Alonso Delgado; Heather Glon; Mengjin Zhang; Marymegan Daly (PLoS ONE, 2025)
Acuticulata is a globally distributed group in the actiniarian superfamily Metridioidea comprised of taxa with ecological, economic, and scientific significance. Prominent members such as Exaiptasia diaphana and Diadumene lineata serve as model organisms for studying coral symbiosis, bleaching phenomena, and ecological invasions. Despite their importance, unresolved phylogenetic relationships and outdated taxonomic frameworks hinder a full understanding of the diversity and evolution of the taxa in this clade. In this study, we employ a targeted sequence-capture approach to construct a robust phylogeny for Acuticulata, addressing long-standing questions about familial monophyly and comparing the results to results from a more conventional five-gene dataset. Specimens from previously underrepresented families and global regions, including the Falkland Islands, were included to elucidate evolutionary interrelationships and improve resolution. Our results support the monophyly of Aliciidae, Boloceroididae, Diadumenidae, Gonactiniidae, and Metridiidae. Our results reiterate the need for taxonomic revision within the family Sagartiidae, as the specimens we included from this family were recovered in four distinct clades. Based on our results, we transfer Paraiptasia from Aiptasiidae to Sagartiidae. These findings emphasize the utility of genome-scale data for resolving phylogenetic ambiguities for morphologically problematic taxa and suggest a framework for future integrative taxonomic and ecological studies within Acuticulata.